Tiến hóa cổ địa lý đảo Cù Lao Chàm (Hội An, Quảng Nam) trong Neogen - Đệ Tứ - Ngọc, Nguyễn; Miên, Đào Thị; Cử, Nguyễn Hữu (Vietnam Journal of Earth Sciences, 2003)
Paleogeographycal evolution of the Gu Lao Cham lsland (Hoi An, Quang Nam) during Neogene-Quaternary